The Rhetoric of Temporal Paradoxes in the Novel of Aqilat - Zaid, Fadhl Yahya; Al-Amari, Anisa Mohammed Ahmed (Arts for Linguistic & Literary Studies, 2021)
This research deals with the approach of temporal paradoxes in the novel of Aqilat by the Yemeni writer Nadia Yahya Hussein Al-Kawkabani in order to analyze the eloquence of the narrative in it. The research was divided into an introduction and two sections: the first section discussed the rhetoric of the paradox of narrative retrieval. The second section discussed the rhetoric of the paradox of narrative anticipations. It was found that the temporal paradoxes in this novel were characterized by a high narrative eloquence. The refractions of time in it constitute a shift from the present time in the narrative line, and a disorder in it. Thus, it contributed to the dismantling of the world of the narrated and the fragmentation of its semantic systems, not with the aim of confusing the mind of the recipient, but in order to break the logical sequence of the narrated and thus eliminate the monotony of the length of the narrative line in the novel.